Determination of Seed Physiological Maturity and Invigoration using Plasma-Activated Water and Ultrafine Bubble Water on Okra Seeds - Nur Syam Ismaniza A., Siti Nur Syam Ismaniza A.; Widajati, Eny; Qadir , Abdul; Purwanto, Y. Aris (Journal of Tropical Crop Science, 2024)
Seeds physical and physiological qualities are primarily determined by seed physiological maturity. Seed enhancement technology has developed rapidly, including using ultrafine bubbles (UFB) and plasma-activated water (PAW) to increase seed viability. This study aimed to determine seed physiology maturity on okra seed to get the optimal harvesting period seeds and to examine the most effective seed enhancement plasma-activated water and ultrafine-bubble Water. The first experiment was arranged using completely randomized design with fruit maturity as the single factor, harvested at 3, 4, 5, or 6 weeks after anthesis (WAA), with three replications. The second experiment used factorial completely randomized design; the first factor is seed lots with different storage times (fresh seed and one-year storage seed), and the second factor seed invigoration using UFB (20 ppm dissolved oxygen) and PAW (10-, 20-, and 30-min exposure) as the second factor. Untreated seeds were used as control. Fifty seeds were used in each treatment. Okra seed physiological maturity was reached at 5 WAA based on seed dry weight, germination capacity, seedling vigor, and speed of germination. The pod color at 5 WAA is olive brown, and seed testa has dark greyish purple. Plasma-activated water at 10 minutes exposure increased the vigor index of seed lots stored for one year by 86% and PAW20 by 87%. Plasma activated water at 10-, 20- and 30-minutes exposures significantly increased the seedling vigor index and germination speed of fresh seeds harvested at 5 WAA.